A proposal for a Brexit deal: Why a free trade area for goods is in the interest of the EU and how to achieve a sound balance of rights and obligations - Jürgen Matthes; Michael Voigtländer (Institut der deutschen Wirtschaft (IW), 2018)
In the political declaration of the Withdrawal Agreement the EU should leave the door open for a free trade area for goods that has been suggested by the UK's Chequers proposals. The EU would profit from such an arrangement due to its comparative advantage in goods. However, in order to achieve the EU's main objective to avoid bandwagon effects, such a trade agreement must not be depicted as a favourable deal for the UK. The narrative of the four freedoms is not indispensable to prevent bandwagon effects. A narrow interpretation can be even counterproductive, if the EU continues to regard a lesser degree of service trade integration (as suggested by the UK) as a key stumbling block for a free trade area for goods. On closer inspection, less service trade integration is not a real problem, because it would not lead to relevant competitive distortions as feared by the EU, as other areas like labour costs and social contributions are more relevant cost factors which are not (and should not) be harmonised in the EU. Moreover, the UK proposes to agree to binding rules to prevent distortions of a level playing field in terms of environmental regulations, state aid and competition policy. [...]
Keywords: F1; F2; O52; 330